2018
DOI: 10.3839/jabc.2018.005
|View full text |Cite
|
Sign up to set email alerts
|

Beauty food activities of wild-cultivated Ginseng (Panax ginseng C.A. Meyer) ground part

Abstract: This study aimed to investigate the beauty food activities of wild-cultivated ginseng (Panax ginseng C.A. Meyer). wild-cultivated ginseng extracts were analyzed for antioxidant, skin whitening, anti-wrinkle effect was measured in water and 70% ethanol extract. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging and 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical decolorization activities of water and 70% ethanol extracts were 16.69 and 2.18% as well as 4.04 and 3.25% at a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…For example, in skin cancer, ginseng has a chemopreventive effect, while WSG has a chemotherapeutic effect [41]. WSG shows diverse effects such as anti-oxidation [42], anti-inflammation [43], anti-tumor, and immune-enhancing activities [44]. Moreover, WSG has been used in the treatment of various health-related problems, including dry eye syndrome [45], obesity [46], high blood pressure [47], and cancer [48].…”
Section: Effects Of Wild-simulated Ginsengmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in skin cancer, ginseng has a chemopreventive effect, while WSG has a chemotherapeutic effect [41]. WSG shows diverse effects such as anti-oxidation [42], anti-inflammation [43], anti-tumor, and immune-enhancing activities [44]. Moreover, WSG has been used in the treatment of various health-related problems, including dry eye syndrome [45], obesity [46], high blood pressure [47], and cancer [48].…”
Section: Effects Of Wild-simulated Ginsengmentioning
confidence: 99%
“…Moreover, WSG has been used in the treatment of various health-related problems, including dry eye syndrome [45], obesity [46], high blood pressure [47], and cancer [48]. WSG has also been studied for human health and as a cosmetic due to its anti-wrinkle effect [42]. Additionally, many studies have reported the effects of WSG on the environment.…”
Section: Effects Of Wild-simulated Ginsengmentioning
confidence: 99%
“…mountain-cultivated ginseng) 및 산에서 자연적으로 자란 산삼 (wild ginseng)으로 분류된다 [1]. 산양삼이라는 용어는 장뇌삼, 산양산삼 및 산양삼 등으로 불리던 것을 산림청에서 용어를 정 립하고 이를 산양삼으로 사용하도록 규정하였다 [2].…”
unclassified